EFEKTIVITAS TERAPI OKSIGEN HIPERBARIK (HBOT) TERHADAP PENYEMBUHAN LUKA KAKI DIABETIK: LITERATURE REVIEW - Selvia, Heni; Syam, Yuliana; Yusuf, Saldy (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Diabetic Foot Ulcer (DFU) is one of the complications that cause big problems in diabetics. One of the management of DFU management is by utilizing hyperbaric oxygen therapy (HBOT) which is an additional therapy that has been proven to be used in the treatment of DFU. However, the results of its benefits and use are still being debated, so the purpose of this review is to evaluate the effectiveness of HBOT on healing diabetic foot wounds. The method of this research is to use a literature review design. By using three international databases, namely PubMed, Science Direct, and Ebscohost, six articles were included. The results of the review explained that from six articles conducted by the literature review, it was reported that hyperbaric oxygen therapy (HBOT) can accelerate the healing process of diabetic foot wounds (DFU), by reducing wound size, lowering levels of C-reactive protein (CRP) and white blood cells (WBC)), induces angiogenesis of EGF, VEGF, PDGF, FGF-2 and CXCL10 and changes serum interleukin 6 (IL-6) and VEGF levels to be greater. Conclusion (HBOT) is an appropriate adjunct therapy, which can provide effectiveness in the treatment of DFU by accelerating the healing of DFU and preventing further infection in DFU, so as to reduce the risk of amputation.